2013
DOI: 10.1194/jlr.m035865
|View full text |Cite
|
Sign up to set email alerts
|

SCD1 activity in muscle increases triglyceride PUFA content, exercise capacity, and PPARΔ expression in mice

Abstract: This article is available online at http://www.jlr.orgTo combat the rise in obesity and metabolic diseases, a large number of studies have attempted to defi ne the etiology of impaired glucose metabolism, dyslipidemia, and lipodystrophy ( 1-5 ). The results of these studies have generally shown that development of type 2 diabetes mellitus (T2DM) is dependent on a multitude of factors, including obesity due to overnutrition combined with physical inactivity; consumption of a high-fat/high-carbohydrate diet; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…Our laboratory recently completed a project involving an SCD1 transgenic mouse model that overexpresses SCD1 specifically in skeletal muscle (SCD1 Tg) (66). When fed standard chow, results from this study showed that these animals had reduced levels of SFA in their muscle along with increased Review E771 SKELETAL MUSCLE SCD1 AND METABOLISM MUFA compared with control mice, as expected.…”
Section: Future Directionsmentioning
confidence: 66%
See 1 more Smart Citation
“…Our laboratory recently completed a project involving an SCD1 transgenic mouse model that overexpresses SCD1 specifically in skeletal muscle (SCD1 Tg) (66). When fed standard chow, results from this study showed that these animals had reduced levels of SFA in their muscle along with increased Review E771 SKELETAL MUSCLE SCD1 AND METABOLISM MUFA compared with control mice, as expected.…”
Section: Future Directionsmentioning
confidence: 66%
“…The increased mitochondrial content translated into an increased ability to oxidize 14 C-labeled stearic acid in ex vivo cultured skeletal muscle. SCD1 animals also demonstrated a very large increase in endurance exercise capacity, which may have been partially due to increased mitochondrial content and PPAR␦ expression (66). Evidence demonstrates that insulin resistance directly correlates with increased SFA within IMTG (43), whereas MUFA prevents insulin resistance initiated by SFA in skeletal muscle (11).…”
Section: Future Directionsmentioning
confidence: 97%
“…To clarify possible mechanisms of TG accumulation in the kidney, we examined the expression of enzymes that are key regulators of FA metabolism (SCD1) (19)(20)(21), increased uptake (CD36), and decreased expression of enzymes of fat ␤ -oxidation (ACO and CPT1). The expressions of PPAR ␣ and PPAR ␦ and their downstream enzymes ACO and CPT1 were decreased and correlated with the decline in eGFR ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, it was shown that increasing SCD1 activity through dietary factors or exercise could be protective against excessive weight gain and type 2 diabetes [47]. It was observed previously that overexpression of SCD1 inhibited inflammation and ER stress response subsequent to palmitate exposure [47].…”
Section: Scd1 In Muscle Metabolismmentioning
confidence: 99%